MENINGKATKAN DAYAGUNA FASILITAS PANGKALAN PENDARATAN IKAN DUMAI PROPINSI RIAU - Jonny Zain (Fakultas Perikanan dan Kelautan, Universitas Riau, 2009)
Purpose of this research is to know the operational problems of the fishingport, as well as is to find the solution for increasing efficiency of the fishing portin Dumai. This research was conducted by survey methods at fishing port inDumai on May to September 2009. Data analysis was used technique analysis,facility utilization analysis and SWOT analysis.The survey showed that the utilization of pear, water deep, fish markethall, ice factory, fresh water tank, fuel supply were 97.8%, 63.3%, 53.2%, 135%,92,4% and 114,9% respectively. Utilization of the fishing port facilities wasincreased around 23, 3% to100, 7% if it’s compared to 2004. However, fishmarket and cold storage was not utilized (0%), because of operational basic of thefishing port was not completed and no institutions policy from regulations as afish market center. Therefore, it requires a policy to force fishing port in Dumai asa fish market center.